The Consumer in a Globalizing World: Insights from a Multi-Level Marketing Firm - Angela, Nnamocha Obiageli (Archives of Business Research, 2019)
As noted by Kamila, Mask and Michael (2014), the phenomenon of globalization is of paramount importance for today’s marketing practitioners. Globalization reducesthe gap between nations, occasioned by vast advancements in technology, transportation and communication, while ease of exchange and access to information and world markets are the fruits/dividends of globalization. As globalization increases, people across various nations tend to become similar in their purchases and consumption behavior (Mohamed et al 2013). Interestingly, these people have diverse orientations and culturesand yet, they tend to behave alike in consumption contexts. This goes to show that consumer satisfaction and value in a globalised world seem to transcend geographical horizons. As noted by Mariola and Danielak (2015), there is no single common position on how purchasing decisions are determined by global trends and to what extent are the results of culture and conditioning. Consumers having access to communication and technology, therefore, automatically conduct more research, rationally searching for the best deals. In this study, the researcher used a combined approach, i.e. theoretical framework, empirical evidence and experimentation or primary data generation through fieldwork. The sample consists of about 1,350 consumers and 150 marketers; totaling 1,500 respondents. The hypotheses of the study focus on the dual (positive and negative) effects which globalization has on both the consumers and the marketers alike, and how these would rub-off on the nation’s economy. In addition to simple descriptive statistics, correlation analysis and the z-test are used in testing the data so generated.